Endometrial safety of ospemifene. Issue 1 (January 2015) - Constantine, Ginger D.; Goldstein, Steven R.; Archer, David F.
Abstract Objective This study aims to assess the endometrial safety of ospemifene based on phase 2/3 clinical trials of postmenopausal women with up to 52 weeks of exposure to ospemifene 60 mg/day versus placebo. Methods Endometrial safety was evaluated in a development program of six randomized, double-blind, placebo-controlled, parallel-group studies of postmenopausal women aged between 40 and 80 years who had vulvar and vaginal atrophy. Participants were randomized 1:1 to ospemifene 60 mg/day or placebo in one 6-week trial and three 12-week trials; one of the 12-week trials had a 40-week extension study. In a separate 52-week trial, women were randomized 6:1 to ospemifene 60 mg/day or placebo. Endometrial safety was assessed by endometrial histology (biopsy), transvaginal ultrasound, and gynecologic examination. Results In these trials, 1, 242 women who received ospemifene 60 mg/day and 924 women who received placebo were evaluable for safety. Endometrial hyperplasia occurred in less than 1% of women treated with ospemifene; no endometrial cancer was reported. The mean (SD) increase in endometrial thickness among women treated with ospemifene was 0.51 (1.54) mm at 12 weeks, 0.56 (1.61) mm at 6 months, and 0.81 (1.54) mm at 12 months. Women who received placebo had a mean (SD) increase of 0.07 (1.23) mm at 12 months. Conclusions These clinical trial data indicate that up to 52 weeks of treatment with oral ospemifene 60 mg/day was safe for the endometrium. There was no increase in the incidence of endometrial cancer or hyperplasia among postmenopausal women treated with ospemifene compared with placebo.